Integrating Hospital Safety Index and HRM to Enhance Disaster Preparedness - Yoki Muchsam; Mulfi Sandi Yuda; Fani Ananda Prisilia; Dina Destiani (Gema Lingkungan Kesehatan, 2026)
Flooding is a catastrophic environmental health risk in Bekasi Regency and has continually posed adverse impacts on hospital operation interruptions and patient safety. These effects highlight the importance of environmentally literate and people-focused preparedness. The purpose of this study was to evaluate a combined model for managing the hospital safety and human resource planning which introduced the Hospital Safety Index (HSI) and human resource management into a competency-based approach, aiming that hospitals be able to provide their essential services throughout environmental events. This was a qualitative case study on Bekasi Regional General Hospital in flood-prone area. Three in-depth interviews were conducted with hospital decision makers, doctors and nurses as well as K3RS staff; two Focus Group Discussions; questionnaires and document analysis. Based on a modified HSI instrument (40 HOSDIP items), SWOT-TOWS matrices, and Balanced Scorecard (BSC) indicators, environmental safety readiness and HRM-driven response mechanisms were evaluated in this research. The results reveal that the HSI of the hospital is in Category B (moderate safe) mainly due to important gaps in Staff training, Emergency operations coordination and Logistic which directly impacts on the capacity of the facility to manage environmental health risks during flooding. The embedding of HRM in HSI-based assessments enhanced strategic fit and facilitated the development of more flexible preparedness capabilities aligned with BSC themes. The results show that HSI-HRM-BSC composes an evidential model for enhancing hospital resilience to environmental hazards. That preparedness is not only based on safe infrastructure, but also involves the management of competent, coordinated and adaptable human resources which stresses the centrality of people‐centred approaches for mitigating health impacts from environmental disasters.